Competition among digital services: Evidence from the 2021 Meta outage - Dominik Rehse; Sebastian Valet (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2025)
On October 4, 2021, all services provided by Meta Platforms, Inc. (then Facebook, Inc.) became unavailable unexpectedly for all its worldwide users for a period of about six hours. We use detailed high-frequency tracking data from smartphones, tablets and desktop computers of thousands of Meta users from Spain and the United States to study their behavioral responses during the outage. We find (1) the strongest substi- tution occurs within social media and messaging services, (2) evidence of substitution across service categories, (3) substitution patterns that vary across demographic groups, (4) substantially higher substitution rates among multi-homers, (5) substitution rates that increase over the course of the outage, (6) distinct differences in substitution patterns between countries, and (7) increased usage of non-Meta digital services after the outage. To our knowledge, this study presents the first comprehensive revealed-preference analysis of substitution patterns when an entire user population simultaneously seeks alternatives to major digital services.
Keywords: L40; L82; L86; 330; Digital services; Competition; Substitution; Attention markets; Outage